Influence of Brand Image, Price, Consumer Satisfaction, Product Quality and Promotion on Repurchase Decisions (Case Study on Teh Botol Sosro Consumers) - Dani Zahuri Mohammad; Slamet Abadi; I Putu Eka Wijaya (UNIVED Press, Dehasen University Bengkulu, 2023)
Teh Botol Sosro has successfully maintained its popularity in the highly competitive packaged tea market in Indonesia. To understand the factors influencing consumer repurchase decisions, a study was conducted at ÆON Mall Jakarta Garden City. This research evaluated brand image, pricing, customer satisfaction, product quality, and promotion as factors affecting consumer decisions, both collectively and individually.Use of primary data in this study were obtained through interviews with 100 randomly selected Teh Botol Sosro consumers, supplemented by data from the Central Statistics Agency (BPS) and literature reviews. The research results indicate that these factors influence repurchase decisions. When assessed individually, brand image and pricing do not have a significant impact, while customer satisfaction, product quality, and promotion have a substantial influence on repurchase decisions. These findings have important implications for Teh Botol Sosro and other industry players in formulating more effective marketing strategies to maintain and expand their market share.